The Employment of Leukotriene Antagonists in Cutaneous Diseases Belonging to Allergological Field - Eustachio Nettis; Maddalena D'Erasmo; Elisabetta Di Leo; Gianfranco Calogiuri; Vincenzo Montinaro; Antonio Ferrannini; Angelo Vacca (Hindawi Limited, 2010)
Leukotrienes (LTs) are potent biological proinflammatory mediators. LTC4, LTD4, and LTE4 are more frequently involved in chronic inflammatory responses and exert their actions binding to a cysteinyl-LT 1 (CysLT1) receptor and a cysteinyl-LT 2 (CysLT2) receptor. LTs receptor antagonists available for clinical use demonstrate high-affinity binding to the CysLT1 receptor. In this paper the employment of anti-LTs in allergic cutaneous diseases is analyzed showing that several studies have recently reported a beneficial effects of these agents (montelukast and zafirlukast as well as zileuton) for the treatment of some allergic cutaneous related diseases-like chronic urticaria and atopic eczema although their proper application remains to be established.